Wealth Tax Mobility and Tax Coordination - David R. Agrawal; Dirk Foremny; Clara Martínez-Toledano (Center for Economic Studies and ifo Institute (CESifo), 2024)
We study the effects of decentralized wealth taxation on mobility and the effectiveness of tax coordination at mitigating tax competition. We exploit the reintroduction of the Spanish wealth tax, after which all regions except Madrid levied positive tax rates. We find the mobility responses to wealth taxes are within the range of prior estimates with respect to income taxes. However, wealth tax mobility responses generate losses to personal income tax revenues that are six times larger than the direct losses to wealth taxes. Madrid could achieve higher total regional revenues by agreeing to a harmonized positive tax rate.
Keywords: E21; H24; H31; H73; J61; R23; 330; wealth taxes; mobility; fiscal decentralization; fiscal federalism; tax coordination